Valuable orientations of student youthto post-crisis for kyrgyzstan period (2010-2011) - Nazgul T. Cholponkulova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article examines the features of the value orientation of student youth in the northern and southern regions of Kyrgyzstan in the post-crisis period for the country (2010-2011). In the course of the research, it was revealed that the value kernel of students' consciousness, regardless of regional representation, is identical, which indicates the value unity of the student youth of the country. Also, data were obtained that testify to differences in the structure of instrumental values and the selection by students of different regions of different strategies and ways to achieve goals. According to the author, it is this feature that makes up the uniqueness and behavioral difference of the youth of the northern and southern part of the country. Comparative analysis with the results of the previous period showed the transformation and reorientation of terminal values of student youth from a subjective orientation to collectivism. In the structure of instrumental values of the test subjects of the north of the country, there is also a change in value orientations from personal and emotional orientation to professional, and in the southern regions to collectivist orientation.